Highly concise and practical route to clavaminols, sphinganine and (+)-spisulosine via indium mediated allylation of alpha-hydrazino aldehyde and a theoretical insight into the stereochemical aspects of the reaction - Pandey, Menaka; Chowdhury, Partha Sarathi; Dutta, Achintya Kumar; Kumar, Pradeep; Pal, Sourav (RSC Advances, 2013)
A conceptually different approach has been employed for the synthesis of 1,2-amino alcohols by proline-catalyzed alpha-amination of aldehyde and one-pot indium mediated allylation of the crude alpha-hydrazino aldehydes. DFT based quantum chemical calculations have been performed to obtain a quantitative explanation of the stereoselectivity of the reaction.